Enhanced expression of the sphingosine-1-phosphate-receptor-3 causes acute myelogenous leukemia in mice - Vorbach, Samuel; Gründer, Albert; Zhou, Fengbiao; Koellerer, Christoph; Jutzi, Jonas S.; Simoni, Manuela; Riccetti, Laura; Valk, Peter J.; Sanders, Mathijs A.; Müller-Tidow, Carsten; Nofer, Jerzy-Roch; Pahl, Heike L.; et al. (Leukemia, 2020)
Acute myeloid leukemia (AML) carries a 10-100 fold lower mutational burden than other neoplastic entities. Mechanistic explanations for why a low number of mutations suffice to induce leukemogenesis are therefore required. Here we demonstrate that transgenic overexpression of the wild type sphingosine-1-phosphate receptor 3 (S1P3) in murine hematopoietic stem cells is sufficient to induce a transplantable myeloid leukemia. In contrast, S1P3 expression in more mature compartments does not cause malignant transformation. Treatment with the sphingosine phosphate receptor modulator Fingolimod, which prevents receptor signaling, normalized peripheral blood cell counts and reduced spleen sizes in S1P3 expressing mice. Gene expression analyses in AML patients revealed elevated S1P3 expression specifically in two molecular subclasses. Our data suggest a previously unrecognized contribution of wild type S1P3 signaling to leukemogenesis that warrants the exploration of S1P3 antagonists in preclinical AML models.
Published online: 21 October 2019
Gesehen am 14.04.2020